"Making God's Love Manifest": American Expressions and Productions of Charisma in Sri Mata Amritanandamayi Devi's Global Following - (:unkn) unknown (My University, 2021)
While situating it in a changing American religious landscape marked by increasing participation in metaphysical religion, this dissertation examines the appeal of contemporary Indian godperson, Sri Mata Amritanandamayi Devi (Amma), to Americans. Although replete with portraits of individual Indian spiritual leaders’ charisma, the anthropology of religion literature seldom addresses the processes whereby such figures’ charisma gets produced. Drawing on thirteen months of multi-sited ethnographic research conducted between 2015-2016, this dissertation uses Max Weber’s theory of charisma to answer the following questions: what extraordinary capacity do American devotees attribute to Amma; what is the process whereby they and she co-produce this particular expression of her charisma; and what is the role of seva (selfless service) in this process? Three key findings resulted from this study. First, over the course of their progression through what I identify as the “admirer,” “initiate,” “ashramite,” and “renunciate” stages the American Devotee Life Cycle, American devotees modify their seva practices to perform them on behalf of a wider variety of beneficiaries in a wider variety of contexts as well as in more of an ongoing manner. Second, American devotees attribute to Amma the extraordinary capacity to transform people. By this, I mean the extraordinary capacity to encourage spiritual seekers not only to understand themselves and the world in which they live but also to act in that world according to what I term a “sevite habitus” informed by the spiritual truth that all are essentially one. According to American devotees, such is “god’s love,” which Amma makes manifest in them - by virtue of her necessarily transformative divine powers, or “grace” - in the form of a desire to perform seva practices on behalf of all always. This is Amma’s charisma and the reason for her appeal to Americans. Third, the process whereby Amma’s charisma gets produced is collaborative. Motivated by proxemic desire, American devotees pursue opportunities to be near Amma. These include opportunities to perform seva practices in her presence. Upon interpreting praising and scolding behaviors that Amma displays as guidance to do so, American devotees diversify their seva practices. They also perform their seva practices more frequently. As a result, they perform the transforming personhoods that they attribute to Amma. Together, these findings contribute to the anthropology of religion literature on charismatic Indian spiritual leaders by illustrating the role that spiritual seekers play in the construction of the power that such figures wield in the material world.
Keywords: Charisma; Conversion; Gurus; Indian spiritual leaders; Service; Seva